Attica: A Hot Spot for Forest Fires in Greece - Margarita Arianoutsou; George Athanasakis; Dimitrios Kazanis; Anastasia Christopoulou (Fire)
(1) Background: Forest fires are widespread in Mediterranean-climate regions and are becoming very common in urban and peri-urban areas. (2) Methods: Wildfires in Attica since 1977 are mapped and types of vegetation burned are reported. (3) Results: Fires are becoming larger. During the period of study (1977–2024), 45% of the burned area was covered with Pinus halepensis forests, 1.4% with Abies cephalonica forests, and 18.5% with shrublands. A relatively high percentage of the burned area (BA) affected more than once consisted of pine forests (65%). Ten percent of the total BA lies within the boundaries of the Natura 2000 network, Europe’s most important network of protected areas, of which 38.9% was burned. At the interannual scale, the BA in Attica is negatively correlated with relative humidity, while reduced precipitation may contribute to the expansion of wildfires. (4) Conclusions: Fires are becoming larger over time, with low humidity increasing the higher fire risk. Since the changing climate is expected to create more severe and uncontrollable conditions, mitigation and adaptation measures should be planned and be introduced immediately.